In Search of Autonomy: Dancing With Rules - Heldal, Frode; Dehlin, Erlend (Frontiers in Psychology, 2021)
Purpose: Autonomy in organisations cannot exist without rules nor relationships. Yet, previous research tends to elicit understandings of autonomy as freedom from external constraints to enact free individual will. And there are numerous positive effects related to autonomy at work. But research has not kept pace with modern-day organisations that are highly flexible and dynamic. Current understandings of autonomy are static. Autonomy is mainly regarded as something individuals possess, more or less constricted by rules. Our purpose is to contribute a more flexible and practice-oriented concept of autonomy to answer the research question: How is autonomy developed and practiced in relation to formal rules in high-risk organisations? Design: To investigate autonomy as a dynamic and flexible concept, we draw on two case studies comprised of a total of 52 interviews and more than 10 hours of observation. Cases include a factory and a hospital unit. Findings: We suggest, based on the data, that autonomy is a relational phenomenon. We suggest four different autonomy-rule dynamics: Passive, loyal, self-promoting and co-generative learning. Research implications: Regarding autonomy as relational rather than individual contributes to our understanding of organisations as always in the making. In this, we emphasize the interactive element of autonomy. Practical implications: Practitioners and managers may use our suggestions to work with autonomy in a different way, spurring creativity and improvisation by using rules in a constructive fashion. Originality: Little research has paid attention to the concept of autonomy (despite its importance), and arguably a trend in the available research concerns a commodification of the phenomenon, primarily aligning autonomy with (degrees of) negative freedom and individual decision making. We unpack the concept with an attention to interaction – what we have called dancing with rules.